Islamic Religious Education and Interreligious Tolerance in a Multi-Religious Country: Challenges, Typological Implications, and the Proposed Strategy - Mohamad Iwan Fitriani (Universitas Islam Negeri Mataram, 2023)
This research seeks to examine contemporary challenges relating to the realization of intra- and interreligious tolerance within the Indonesian Islamic Religious Education (IRE) system. To this end, I identify three areas requiring revisiting: the challenges facing teachers of IRE in regard to the promotion of intra- and interreligious tolerance, the implications of these challenges for typologies of student tolerance and intolerance, and the proposed strategy to cope with the challenges. The study utilizes a qualitative approach across multiple sites. Data were collected in the form of in-depth interviews, document analysis, and observation at a madrasah (MA, Indonesian: Madrasah Aliyah) and two high schools (SMA, Indonesian: Sekolah Menengah Atas). Data were analyzed through six steps of Braun and Clarke's thematic analysis. This research finds that: (1) challenges related to the emergence of intra- and interreligious intolerance are traced to the domination of the mono-religious education model within the study of IRE in MA and SMAs; (2) the domination of this mono-religious education model is implicated in a number of tolerance and intolerance student typologies, such as active-passive intolerance and active-passive tolerance and active intra- and interreligious tolerance; (3) the proposed strategy to cope with challenges faced by IRE teachers to promote intra and inter-religious tolerance is mutual supporting religious education model, which could be supported via macro-, meso-, and micro-educational system policy and regulation.